THE ROLE OF THE FAECAL SAMPLES CULTIVATION IN THE DIAGNOSTICS OF CLOSTRIDIOIDES DIFFICILE INFECTION - Mihajlov, Kiril; Trajkovska Dokic, Elena; Labachevska Gjatovska, Liljana; Kostovski, Marko; Jovchevski, Radomir; Kovacheva-Trpkovska, Danica; Cvetanovska Ilievski, Biljana; Krsteva, Nadica; Dimitrievski, Kristijan (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Introduction:  Clostridioides difficile is one of the most important intra-hospital pathogens. A few years ago, a new diagnostic algorithm for Clostridioides difficile infection (CDI) was introduced by ESCMID, stating that cultivation of the bacteria is not necessary for the diagnosis of CDI. Aim:  We aimed to explore the role of the cultivation of faecal samples in the diagnosis of CDI. Materials and Methods: In 4 years, we have cultivated 80 different strains of C. difficile from as many patients. Initially, 1380 faecal samples from CDI-suspected patients were planted on selective and non-selective blood agar media and were accordingly incubated in order to isolate the strains. Quick immuno-chromatographic tests were performed on each faecal sample for detection of GDH (glutamate dehydrogenase) and C. difficile toxins A and B as well as on each confirmed C. difficile isolate (from one colony-toxins detection only). Results: In 14 of the 80 faecal samples from which the isolates originated, toxins A and B have not been detected. In 8 of these 14 strains, toxins A and B were detected only from the culture. Only 6 strains were confirmed as non-toxigenic. Conclusions: Although there was no statistical significance, the detection rate of C. difficile toxins A and B was higher from the culture than from the faecal samples by up to 10%. Cultivation of the samples for C. difficile could reduce the rate of false negative findings for CDI.  Keywords:  Clostridioides difficile infection, ESCMID diagnostic algorithm, toxigenic culture.